THE EFFECT OF SHARIA STOCK STATUS AND THE COMPANY'S NON-SHARIA DEBT RATIO ON ESG SCORE - Raniri, Rumi; Violita, Evony Silvino (Berkala Akuntansi dan Keuangan Indonesia, 2025)
Daftar Efek Syariah (DES) does screening to create Indeks Saham Syariah Indonesia (ISSI). Following Sharia values, it is necessary to see whether it can also reflect better non-financial reports. This study examines whether the ESG performance of sharia-compliance companies is higher. Unlike previous studies, this study also tests whether non-sharia debt ratio (that also reflect sharia compiance) affects the ESG score instead of leverage. This study uses Ordinary Least Square (OLS) regression with fixed effect analysis to compare the ESG score among Indonesian companies. The results prove that, while non-sharia debt ratio affects ESG scores especially the environmental and social pillars, DES screening affects ESG scores especially the social pillar only. This finding enriches studies on ESG and sharia compliance. This study broadens the perspective of stakeholders in Indonesia who pay attention to maqashid sharia and provides implications for DES to integrate ESG dimensions in determining sharia-compliant companies.